A ratiometric luminescence nanoprobe based on layered terbium hydroxide nanosheets for quantitative detection of an anthrax biomarker. Issue 1 (4th January 2022) - Li, Jinyan; Gu, Qingyang; Heng, Hui; Wang, Ziwei; Jin, Haibo; He, Jing
Abstract : A novel ratiometric luminescence nanoprobe based on layered terbium hydroxide nanosheets can selectively detect dipicolinic acid, which is an anthrax biomarker. Abstract : A novel ratiometric luminescence nanoprobe based on layered terbium hydroxide (LTbH) nanosheets was constructed for quantitative detection of dipicolinic acid (DPA), which was an anthrax biomarker. The LTbH nanosheets can be obtained by the exfoliation of the dodecyl sulfate (SDS) intercalated LTbH in formamide (FM). Upon the addition of DPA, the intrinsic green luminescence of Tb 3+ can be sensitized due to the antenna effect. The luminescence intensity of FM at 332 nm as a reference remained almost constant, leading to ratiometric luminescence response toward DPA. The prepared luminescence nanoprobe was able to detect DPA with a linear relationship in the wide range of 1–100 μM, and the detection limit was 36.67 nM. In addition, the probe showed high selectivity and sensitivity for the detection of DPA as an anthrax biomarker and can be applied in actual tap water samples.